Some Issues on Perfection of the Tax System of the Republic of Uzbekistan - Mutalova, D.M.; Azimova, F.P.; M. , Yuldasheva (International Journal of Psychosocial Rehabilitation, 2020)
The article gives an analysis of the development of the economy of the Republic of Uzbekistan in recent years, discloses the role of individual and small business in this development, analyzes the adopted new Tax Concept on reforming the tax system, identifies certain omissions and shortcomings, offers suggestions for further improvement of the Tax Policy.